Implementation of Microservices in Fintech Applications Using Expressis Framework - Bernardus Redika Westama Putra; Evangs Mailoa (Eduvest - Journal of Universal Studies, 2021)
Along with the development of software architecture, the emergence of microservice architecture has become a trend used by developers in recent years. This study aims to analyze the implementation of microservices in Fintech applications using the ExpressJs framework. The method used in this research is descriptive qualitative method. This study uses a library research method that refers to resources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The method used in making the application is DevOps. In this method, there are eight stages of software development, plan, code, build, test, release, deploy, operate, monitor. Based on the discussion and testing that has been carried out, several conclusions can be drawn namely microservice makes application development easier and more flexible by adding services as needed. Make it easier for other applications to access services that have been made via HTTP Requests, another thing is to facilitate application integration between platforms, both mobile, web and desktop.